Synthesis of some 3-(Arylalkylthio)-4-alkyl/aryl-5-(4-aminophenyl)-4H-1,2, 4-triazole derivatives and their anticonvulsant activity - KÜÇÜKGÜZEL, İLKAY; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (My University, 2004)
A series of novel 3-{[(substituted phenyl)methyl]thio}-4-alkyl/aryl-5-(4- aminophenyl)-4H-1,2,4-triazoles 11-20 and several related Schiff's bases, 3-{[(substituted phenyl)-methyl]thio}-4-alkyl/aryl-5-{[[(substituted phenyl/5-nitro-2-furyl)methylene]amino]-phenyl}-4H-1,2,4-triazoles 21-31 were synthesized for evaluation of their biological properties. Structures of the synthesized compounds were confirmed by the use of their spectral data besides elemental analysis. All compounds were evaluated for their anticonvulsant activity by maximal electroshock (MES), subcutaneous pentylenetetrazole (scPTZ) and neurotoxicity (NT) screens. A number of triazole derivatives, exhibited protection after intraperitoneal administration at the dose of 100 and 300 mg/kg in one or both models employed. Compounds 12, 13 and 14 were subjected to oral MES screening in rats at 30 mg/kg and were observed to protect 50% of the animals employed in the experiment. Antimicrobial and antituberculosis activity of these compounds 11-31 were also screened. Some of the tested compounds showed marginal activity against M. tuberculosis H37 Rv. © 2004 Published by Elsevier SAS.
Keywords: 1,2,4-Triazoles; Anticonvulsant activity; Maximal electroshock; Neurotoxicity; Pentylenetetrazole